American Indian medicine ways : spiritual power, prophets, and healing - Trafzer, Clifford E. (The University of Arizona Press, 2017)
The book highlights American Indian spiritual leaders, miracle healings, and ceremonies that have influenced American history and shows their continued significance--Provided by publisher.